Wooden breast myopathy is characterized by satellite cell dysfunction and syndecan-4 shedding - Pejšková, Lucie; Pisconti, Addolorata; Lunde, Marianne; Ho, Ka Yi; Solberg, Nina Therese; Koga, Shiori; Tengstrand, Erik; Carlson, Cathrine Rein; Pedersen, Mona Elisabeth; Rønning, Sissel Beate (Frontiers in Physiology, 2024)
IntroductionSkeletal muscle satellite cells (MuSCs or stem cells) play a crucial role in muscle development, maintenance, and regeneration, supporting both hypertrophy and regenerative myogenesis. Syndecans (SDCs) act as communication bridges within the muscle microenvironment, regulating interactions with extracellular matrix components and contributing significantly to tissue repair and inflammation. Specifically, syndecan-4 (SDC4) is involved in muscle regeneration at multiple stages.MethodsThis study delves into the emerging challenge of wooden breast (WB) myopathy and its connection with SDC4. Our hypothesis proposes that disruptions in MuSC dynamics through SDC4 contribute to the increased incidence of breast myopathies observed in growing broilers. To test our hypothesis, non-affected and affected broilers were systematically selected, and the characteristics of WB myopathy were studied both in vitro and in vivo. SDC4 overexpression in MuSCs and blocking peptides (BPs) corresponding to the SDC4 ectodomain were used for investigating the role of SDC4 in muscle development and its shedding levels.Results and discussionIn vivo examination of affected muscles revealed smaller fibers and changes in metabolic pathways. In vitro studies unveiled disrupted proliferation of MuSCs in WB myopathy, accompanied by the downregulation of several muscle markers. Investigation of the potential role of SDC4 in the pathogenesis of WB myopathy revealed a decreased tendency in SDC4 gene expression and increased shedding of its ectodomain. Moreover, we showed that SDC4 overexpression is linked to reduced proliferation in MuSCs and affected myogenesis. We detected an impaired proliferation of WB-affected MuSCs, revealing critical insights into the dysfunctional state of these cells in myopathy. Additionally, by treating MuSCs with blocking peptides derived from the SDC4 ectodomain, we identified altered proliferation. Taken together, this work contributes with valuable knowledge on the molecular mechanisms underlying WB myopathy and the role of SDC4 in this chicken myopathy.